1996
DOI: 10.3181/00379727-211-43979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amiodarone-Induced Phospholipidosis on Pulmonary Host Defense Functions in Rats

Abstract: The effect of the induction of pulmonary phospholipidosis by amiodarone on selected pulmonary host defense functions was studied in male Fischer-344 rats. One week of daily amiodarone treatment resulted in a 4.5-fold increase in total phospholipid in alveolar macrophages recovered from the lungs by bronchoalveolar lavage. The presence of the phospholipidosis had no effect on the phagocytosis of heat-killed yeast cells, the induction of luminol-dependent chemiluminescence, or the spontaneous release of interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Others have shown no impairment of pulmonary host defence mechanisms in the rat, 39 nor changes in the phagocytosis of heat-killed yeast cells 39 by AM with a foamy appearance. Results from our model differ from these other studies in that we showed that amiodarone significantly impaired the ability of the macrophages to phagocytose microspheres.…”
Section: Discussionmentioning
confidence: 95%
“…Others have shown no impairment of pulmonary host defence mechanisms in the rat, 39 nor changes in the phagocytosis of heat-killed yeast cells 39 by AM with a foamy appearance. Results from our model differ from these other studies in that we showed that amiodarone significantly impaired the ability of the macrophages to phagocytose microspheres.…”
Section: Discussionmentioning
confidence: 95%
“…Actually, experimental listeriosis has been a widely accepted method for studying cellmediated immune responses (27)(28)(29). Several reports have shown that the Listeria infection model is also applicable to the respiratory system for assessing pulmonary host defense mechanisms (20,25,(30)(31)(32) and the importance of cytokines in resistance to bacterial infection (33)(34)(35). The present study demonstrates that Listeria induces innate pulmonary immunity and may initiate T-cell-mediated immune responses in Brown-Norway rats, thus allowing one to characterize the mechanism(s) by which DEP exposure alters the pulmonary host defense system.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental listeriosis has been a widely accepted method for studying T-cell-mediated macrophage activation (24). Several studies have used the rat Listeria infection model to assess pulmonary host defense mechanisms (25)(26)(27). Therefore, we use this animal model to test the hypothesis that exposure to DEP suppresses macrophage function, alters T-cell-mediated immunity, and increases the susceptibility of host-tolung infection.…”
mentioning
confidence: 99%